Acquired origin of the left anterior descending coronary artery from the pulmonary artery: A complication of the arterial switch operation - Saltik Levent; Baris Safa; Ozyilmaz Isa; Eroglu Ayse (Wolters Kluwer Medknow Publications, 2011)
The prevalence of coronary anomalies in the transposition of the great arteries is high. Transfer of the coronary arteries during arterial switch operation is the principle step and incomplete transport of the coronary arteries to the neoaortic root results into iatrogenic coronary problems. We present a case with the residual left anterior descending coronary artery originating from the pulmonary artery as a complication of the failure of transfer during the arterial switch operation.